Development And Characterization Of Polylactic Acid/ Porous Corn Starch – Inclusion Complex Blend Film Containing Thymol - Loong, Ye Heng (Universiti Sains Malaysia, 2021)
Polylactic acid is a bio – based polyester, widely applied in the field of food packaging due to its biodegradability, recyclability and non – toxicity nature. However, it is accompanied by drawbacks such as high brittleness, poor thermal stability and barrier properties. In the past, various attempts of improving the functional properties of polylactic acid has been made. Blending of polylactic acid with porous corn starch, which is a type of modified starch equipped with large pore cavities suitable for the formation of inclusion complex, however, has yet been explored. The aim of this research was to fabricate a polylactic acid/porous corn starch – inclusion complex blend film with thymol as the active compound via co – precipitation for the formation of inclusion complex and compression molding for film formation, to determine its effect on the mechanical, thermal, and water vapor barrier properties of polylactic acid. Based on the Fourier - transform infrared spectroscopy result, absorption peaks observed in PLA – inclusion complex film samples, which corresponded to C=O stretching (1749.44 cm-1), C-H bending (1452.40, 1381.03, and 1359.82 cm-1), C-O stretching (1267.23, 1182.36, 1128.36, and 1082.07 cm-1), CO-O stretching (1045.42 cm-1), were found to be identical with pure polylactic acid film, indicating a high miscibility between inclusion complex and polylactic acid film. Incorporation of inclusion complex into polylactic acid film was further confirmed through the depression of onset degradation temperature of polylactic acid – inclusion complex film to 292.0℃ due to the presence of thymol in polylactic acid film with a lower degradation temperature.